A toolbox for real-time subject-independent and subject-dependent classification of brain states from fMRI signals - Rana, Mohit; Gupta, Nalin; Dalboni da rocha, Josue Luiz; Lee, Sangkyun; sitaram, Ranganatha (Frontiers in Neuroscience, 2013)
There is a recent increase in the use of multivariate analysis and pattern classification in prediction and real-time feedback of brain states from functional imaging signals and mapping of spatio-temporal patterns of brain activity. Here we present MANAS, a generalized software toolbox for performing online and offline classification of fMRI signals. MANAS has been developed using MATLAB, LIBSVM and SVMlight packages to achieve a cross-platform environment. MANAS is targeted for neuroscience investigations and brain rehabilitation applications, based on neurofeedback and brain-computer interface (BCI) paradigms. MANAS provides two different approaches for real-time classification: subject dependent and subject independent classification. In this article, we present the methodology of real-time subject dependent and subject independent pattern classification of fMRI signals; the MANAS software architecture and subsystems; and finally demonstrate the use of the system with experimental results. * M. Rana and N. Gupta are equally contributing authors.